¿Ingenieros forestales que no conocen el bosque? - Marc J. , Marc J. (2024)
Since its foundation, in 1963, the academic formation of professional foresters in the National Agrarian University of La Molina, Lima, Perú, has been partially performed directly in the forest. This obviously implies higher efforts and costs, but these are considered essential to ensure the quality of the future foresters.